Biodiesel Production from Waste Cooking Oil in the Presence of Composite Catalysts - Castanheiro, j (2019)
Biodiesel production was carried out in the presence of SBA-15-SO3H dispersed in poly (vinyl alcohol) as acid catalyst. The feedstock was waste cooking oil (WCO) and the alcohol used was methanol. The reaction was carried out at 60ºC in a batch reactor. Catalytic activity of composite catalysts (SBA-15-SO3H dispersed in PVA) increased with the amount of solid acid immobilized in polymeric matrix. This behavior was observed in esterification of oleic acid and transesterification of WCO with methanol. Composite material [SBA-15-SO3H]3/PVA showed the highest activity of them, in esterification of oleic acid and transesterification of WCO with methanol. The composite catalyst showed a good catalytic activity after the second use.